Analisis Pengaruh Lokasi Dan Distribusi Terhadap Manajemen Rantai Pasok Pangan Di Masa Pandemi Covid - Fajar adi Prakoso (Politeknik Kutaraja, 2021)
The ongoing covid pandemic has hampered economic activity. One of them is the food supply chain. Food is a basic need that must be fulfilled and cannot be postponed. During the current pandemic, business people need to pay attention to the existing situation and conditions, especially the limitation of economic activity in several regions. The purpose of this study was to determine the food supply chain during the Covid pandemic in terms of location and distribution factors. This research is qualitative research using secondary data with data collection using library research. Data analysis techniques are used through data collection, data reduction stage, data presentation, and the last is the stage of drawing conclusions and verification. The results of this study indicate that based on the location factor of the area that is in the red zone, the food supply chain can still be carried out but it is necessary to ensure that suppliers are in healthy condition and proper delivery procedures such as maintaining cleanliness and safety to avoid the risk of transmission. Based on distribution factors, business actors need to consider various things such as distribution objectives, the status of distribution goals to be aimed at based on the distribution map of covid, distribution access, transportation modes, and areas where the massive distribution of covid distribution is carried out with certain time restrictions and strict health protocols.